1999
DOI: 10.1023/a:1008315525997
|View full text |Cite
|
Sign up to set email alerts
|

Reduced health-related quality of life among Hodgkin's disease survivors: A comparative study with general population norms

Abstract: Long-term HD survivors have poorer HRQOL, primarily in physical health, than the general Norwegian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
83
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 16 publications
7
83
4
Order By: Relevance
“…While this seems to contradict our findings, it has to be noted that, in comparison to the sample investigated by Loge et al (29) and Ganz et al (30), the time since diagnosis (treatment) was much longer in our sample. Therefore the negative effects of the anticancer treatment would have worn off, resulting in better physical condition and emotional wellbeing.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…While this seems to contradict our findings, it has to be noted that, in comparison to the sample investigated by Loge et al (29) and Ganz et al (30), the time since diagnosis (treatment) was much longer in our sample. Therefore the negative effects of the anticancer treatment would have worn off, resulting in better physical condition and emotional wellbeing.…”
Section: Discussioncontrasting
confidence: 99%
“…In two recent studies investigating the QOL of patients with Hodgkin's disease, Loge et al (29) and Ganz et al (30) reported a less favourable outcome. While this seems to contradict our findings, it has to be noted that, in comparison to the sample investigated by Loge et al (29) and Ganz et al (30), the time since diagnosis (treatment) was much longer in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of gender, younger age was associated with higher functioning and lower symptom severity score, and emotional suffering was generally reported to be more severe than physical symptoms. [86] Of note, results in this study did not demonstrate a relationship between type of treatment and HRQOL outcomes. In a study out of the Southwest Oncology Group in the United States, a comparison of HRQOL in patients treated with either EFRT or CMT found persistent fatigue reported by survivors of each treatment modality, but again without differences according to treatment.…”
Section: Health Related Quality Of Lifecontrasting
confidence: 56%
“…Common chronic non-malignant morbidity (cardiovascular disorders, diabetes, allergy, arthritis/ osteoporosis) reduces HRQoL [8]. Marital and educational status should be taken into account when HRQoL data are interpreted [9,10].…”
mentioning
confidence: 99%